2017
DOI: 10.21767/1307-234x.1000124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Algae Based Diets on Growth Performance, Body Composition and Fatty Acid Profile of Indian Major Carp, Rohu Labeo Rohita, Hamilton)

Abstract: Abstract:Six iso-energetic (352 kcal gross energy/100 g feed) and iso-nitrogenous (32% crude protein) experimental diets containing one of the four algae (Anabaena cylindrica, AN; Nostoc salbasa, NS; Spirulina platensis, SP; Westleopsis prolifica, WS) as the major dietary ingredient (40% of the total composition) or algal meal mixture with supplemental protein (AMM+PS) or only algal meal mixture (AMM) were tested against a control diet to find out the suitability of algal meal to develop practical diet for roh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The HIS and ISI values did not differ significantly among the fish of different experimental groups, which is in agreement with the study of Mishra et al, (2017), who observed that L. rohita fed Westleopsis prolifica, algae as a major dietary ingredients showed no significant differences in HSI. Phulia et al, (2017) also found no significant differences in HSI and ISI of L. rohita fed fermented Jatropha kernel meal in replacement of soybean meal.…”
Section: Experimental Groupssupporting
confidence: 92%
“…The HIS and ISI values did not differ significantly among the fish of different experimental groups, which is in agreement with the study of Mishra et al, (2017), who observed that L. rohita fed Westleopsis prolifica, algae as a major dietary ingredients showed no significant differences in HSI. Phulia et al, (2017) also found no significant differences in HSI and ISI of L. rohita fed fermented Jatropha kernel meal in replacement of soybean meal.…”
Section: Experimental Groupssupporting
confidence: 92%
“…Over numerous centuries, a wealth of knowledge regarding the healing properties of plants has been accumulated. The local community possesses extensive traditional knowledge regarding the use of various plants or substances for treating common diseases [ 25 ]. According to research, total phenolic content (TPC) is considered the primary compound in plants capable of inhibiting free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…With optimum environment and protein diet higher yield of fish meat in term of growth can be obtained [17]. Fish growth can be measured as the increase in fish weight and fish length [18]. For this purpose, the physico-chemical parameters like temperature, dissolved oxygen, and pH of water in tanks must be optimum for proper growth of fish fingerlings [19].…”
Section: Discussionmentioning
confidence: 99%